2016
DOI: 10.1128/aac.00186-16
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Plasmodium vivax Malaria Recurrence after Radical Treatment with a Chloroquine-Primaquine Standard Regimen in Turbo, Colombia

Abstract: Plasmodium vivax recurrences help maintain malaria transmission. They are caused by recrudescence, reinfection, or relapse, which are not easily differentiated. A longitudinal observational study took place in Turbo municipality, Colombia. Participants with uncomplicated P. vivax infection received supervised treatment concomitantly with 25 mg/kg chloroquine and 0.25 mg/kg/ day primaquine for 14 days. Incidence of recurrence was assessed over 180 days. Samples were genotyped, and origins of recurrences were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
3
17
0
1
Order By: Relevance
“…232 published P vivax clinical trials were identified, 134 of which included patients treated with chloroquine and were published between Jan 1, 2000, and March 22, 2017 ( figure 1 ). Individual patient data were available from 33 published studies 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 including 6491 patients (21·2%) of the target sample size of 30 656. Additionally, patient data from four unpublished studies including 1780 patients and an additional 117 patients related to patient cohorts from the published studies, but not described in the manuscripts, were available ( figure 1 ; appendix pp 7–9, 13–15 ).…”
Section: Resultsmentioning
confidence: 99%
“…232 published P vivax clinical trials were identified, 134 of which included patients treated with chloroquine and were published between Jan 1, 2000, and March 22, 2017 ( figure 1 ). Individual patient data were available from 33 published studies 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 including 6491 patients (21·2%) of the target sample size of 30 656. Additionally, patient data from four unpublished studies including 1780 patients and an additional 117 patients related to patient cohorts from the published studies, but not described in the manuscripts, were available ( figure 1 ; appendix pp 7–9, 13–15 ).…”
Section: Resultsmentioning
confidence: 99%
“…This indicated very well the surveillance and control of malaria through the strategies of the Thailand National Malaria Elimination Plan [10]. A previous study reported that 24.1% of patients with P. vivax infection had at least one recurrence within 180 days of full treatment, and this was caused by therapeutic failure [25]. Other studies reported that the incidence of recurrence was 0 to 13.5% after treatment with standard malarial regimen [2628].…”
Section: Discussionmentioning
confidence: 96%
“…A study conducted in Brazil showed that relapse episodes mostly occurred between the day 28 and 90 after initiating treatment [9]. Similarly in Colombia, 86% of the first P. vivax recurrent events occurred between day 51 and 110, and 65.5% of these subsequent episodes were genetically classified as relapses [7]. Identification of relapse is challenging as the relapse episodes could be caused by the activation of the parasites that have different genotypes from that of the initial infection [35, 36].…”
Section: Discussionmentioning
confidence: 99%